The determination of several metals in organic separates of selected South African shales - Marchant, James William (Department of Geological Sciences, 2016)
Some or all of the elements Li, Na, K, Rb, Cs, Mg, Ca, Sr, Cr, Mo, Mn, Fe, Co, Ni, Cu, Ag, Au, Zn, Pb and Tl are determined by Atomic Absorption Spectroscopy in soluble organic and total organic separates from thirty-six samples of South African carboniferous shales. The whole rock values for most of these elements in the samples are known and can be compared with the corresponding values of the organic fraction. A colloidal technique is developed to extract fairly pure kerogen from the shales. Rb, Cs, Ca, Cr, Co, Ni, Cu, Zn and Pb are concentrated in the organic fraction. The results for Rb, Cs and Ca are unexpected. The elements are apparently associated with a sub-fraction of the organic fraction. Several new organic geochemical parameters are developed to interpret the results. Interelement correlations in the various fractions of the shales, the relationship between metal content and organic content, the relationship between concentration of metals by organic matter and residence time, and the use of the metal content of the organic fraction as a paleosalinity test are discussed.